Preliminary Ruling in Serbian Civil Procedure - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
This paper analyses the sections of the Serbian Law on Civil Procedure pertaining to the so-called procedure for preliminary adjudication of an issue of law (preliminary ruling procedure), which enable the court of first instance in an ongoing litigation to submit a request to the Supreme Court of Cassation to take a principal stand, according to the procedure for adopting principal standpoints, if in respect of the given issue of law the judicial practice of the trial courts is inconsistent. The legal solution of the Law is subject to critical remarks, primarily in the light of the principle of the independence of judiciary, with regard to the solutions adopted in comparative law.
Keywords: preliminary issue of law; case law; procedure for preliminary adjudication of an issue of law by the Supreme Court of Cassation